American Horror Story and cult television narratives, histories and discourses - Hand, Richard J. 1965-; O'Thomas, Mark (Anthem Press, 2024)
Over the course of ten seasons since 2011, the television series American Horror Story (AHS), created by Ryan Murphy and Brad Falchuk, has continued to push the boundaries of the televisual form in new and exciting ways. Emerging in a context which has seen a boom in popularity for horror series on television, AHS has distinguished itself from its 'rivals' such as The Walking Dead, Bates Motel or Penny Dreadful through its diverse strategies and storylines, which have seen it explore archetypal narratives of horror culture as well as engage with real historical events. Utilising a repertory company model for its casting, the show has challenged issues around contemporary politics, heteronormativity, violence on the screen and disability, to name but a few. This new collection of essays approaches the AHS anthology series from a variety of critical perspectives within the broader field of television studies and its transections with other disciplines
Title from publisher's bibliographic system (viewed on 08 Mar 2024)
Cover -- Halftitle Page -- Title Page -- Copyright Page -- Contents -- Preliminary Matter and Acknowledgements -- Contributors -- Introduction -- Section 1. Industries/Contexts/Consumption -- Chapter 1. 'I'm really not trying to be cheesy in this moustache twisty way, but it gets really bad. Things that you can't even really imagine...' (Sarah Paulson): American Horror Story and the Horror Ensemble Paradigm -- Chapter 2. The American Horror Story Repertory Company -- Section 2. Intertexts and Referents: Gothic, Voodoo, Witches -- Chapter 3. 'Who's the Baddest Witch in Town?': Adaptation, Female Agency and Monstrous Representation in American Horror Story: 'Coven' -- Chapter 4. 'I Know Your Body': Trauma and the Frankenstein Myth in 'Coven' -- Chapter 5. Science, Madness, and the Gothic in American Horror Story's 'Asylum' -- Chapter 6. 'We're more than just pins and dolls and seeing the future in chicken parts': Channelling and Challenging Voodoo Stereotypes In 'Coven' And 'Apocalypse'95 -- Section 3. Society, Politics, Space -- Chapter 7. Desiring Horror and Desirable Retro Slashers: '1984' and the Transformation of Sociocultural Intelligibility -- Chapter 8. (Un)Dead Together: Hospitality, Hauntology and the 'Happily Ever After' in American Horror Story -- Section 4. Gender/Otherness -- Chapter 9. A Feminist and Queer Approach to American Horror Story's Homonormative and US Nationalist Values in the 'Asylum' and 'Cult' Seasons -- Chapter 10. Scaring with Otherness: American Horror Story and the Other Identity -- Chapter 11. 'Bitchcraft': Adolescent Femininity and Fourth-Wave Feminism in Television Horror -- Chapter 12. 'Cut me and I Bleed Dior': The Dark Side of Glamour in American Horror Story -- Chapter 13. Into The Womb: 'Murder House' and the Erotics of Oppression - An American Horror Story -- Index
Keywords: American horror story (Television program); Horror television programs -- United States -- History and criticism